PSYCHOLOGICAL TRAINING OF SPORTS GYMNASTS (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
The article deals with the psychological preparation of sports gymnasts in international tournaments of various levels. A very large share of success depends on this preparation. Emotional stress can reduce the effectiveness of sports exercises, which will lead to a deterioration in performance, and consequently, to a depressive mood.